The Effect of Company Size, Audit Tenure, KAP Reputation and Leverage on Audit Quality (Empirical Study on Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange in 2018-2021) - Gunawan, Henry (LPPM Universitas Buddhi Dharma, 2025)
The purpose of this study is to identify how the influence of company size, audit tenure, KAP reputation and leverage on audit quality. The approach used in this study is a quantitative approach. Financial statements from manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2018-2021 are the population in this study. The sample selection method uses the purposive sampling method which aims to determine the number of samples based on the criteria that have been set, this study includes as many as 23 companies that are in accordance with the sample selection criteria during the set research period, which is 4 consecutive years so that the total sample used in this study is 92 data. Descriptive statistical test, multicollinearity test, and logistic regression analysis were selected as the data analysis techniques used in this study and with SPSS version 25 as the data processing program. The results of this study show that company size, KAP reputation, and leverage have a partial effect on audit quality, while tenure audit has no partial effect on audit quality, and simultaneously all independent variables have an effect on audit quality.